Between Limited Democratisation and Limited Autocratisation. Political Development of the Ukrainian Society - Brzechczyn, Krzysztof (Wydawnictwo Naukowe UAM, 2007)
The aim of this paper is to present political development of the Ukrainian society in years 1991-2004 in the light of conceptual apparatus of non-Marxian historical materialism.
Keywords: Ukraine; Orange revolution; Non-Marxian historical materialism; Soviet Union; Decline of communism